Letter from Bailey & Co. to James Curtis Booth, April 23, 1856 - Bailey & Co. (1856)
Request for an assay of a sample of silver.
Keywords: Booth, James Curtis, 1810-1888; United States Mint; Mint of the United States; Assaying; Silver--Assaying